318 A controlled trial of the effects of neuromuscular training on biomechanical efficiency in adolescent student-athletes. (3rd March 2020) - Janosky, Joseph; Ling, Daphne; Kinderknecht, James; Marx, Robert
Abstract : Background: Neuromuscular training (NMT) has demonstrated efficacy as a preventive intervention for anterior cruciate ligament (ACL) injury, but the mechanisms that serve as protective factors are not well-defined. Objective: The purpose of this study is to investigate the association between NMT and biomechanical efficiency among adolescent student-athletes. We hypothesized that the performance of NMT is associated with improved biomechanical efficiency during fundamental movement performance and agility testing when compared to a group of untrained subjects. Design: This is a controlled trial with secondary school sports teams assigned to intervention or control groups. Setting: This study was conducted with secondary school soccer and basketball teams. Patients (or Participants): 111 participants (53.1% male, mean age 15.6 years) were recruited to participate in this study. Matched pre/post-season data was collected from a total of 74 athletes. Interventions (or assessment of risk factors): The intervention group performed NMT as a component of their warm-up prior to each practice and competition for 12 weeks under the direction of an experienced sports medicine clinician Exercise instruction, technique cues and corrective feedback throughout each training session were provided during each NMT session. The control group performed their customary warm-up under the direction of the team's coaches. Main outcome measurements: Biomechanical efficiency during fundamental movements was assessed using an USFDA-approved wireless sensor system. Agility was assessed using a timed three-cone agility test. All tests were administered prior to and following each sports season. Results: Statistically significant improvements were observed in the intervention group for loading/landing speed ratios during a single leg hop test, ground reaction force, initial peak acceleration, and cadence during a straight-line running acceleration/deceleration test, and time during a three-cone agility test when compared to the control group. Conclusions: Improved biomechanical efficiency in adolescent student-athletes may explain the mechanism by which NMT serves as a protective factor against ACL injury.